Corporate Governance and Humble Leadership as Antecedents of Corporate Financial Performance: Monetary Incentive as a Moderator - Zahoor, Sajjad; Yang, Shuili; Ren, Xiaoyan; Haider, Syed Arslan (Frontiers in Psychology, 2022)
Investors' confidence in the financial market is boosted by good corporate governance (CG). Good governance builds trust and improves an organization's financial performance (FP). However, organizations with bad management lose the trust of their stakeholders because they do not perform well financially. Therefore, the purpose of this study is to examine the influence of CG 89; on FP through mediating the role of humble leadership (HL) and monetary incentive (MI) as a moderator between CG and HL. Data were collected from 300 respondents who were working in various cement manufacturing organizations located in different cities of Pakistan. The analysis was performed using SPSS software version 25 and AMOS version 22 software to work out the study sample size. The result revealed that the framework of CG has a positive impact in terms of FP. Furthermore, HL positively and significantly mediates on CG, and FP is inextricably linked. However, MI acts as a moderator between CG and HL, but despite strengthening, it weakens the impact of CG' on HL. This study contributes toward the literature, specifically toward the expectancy theory literature. Finally, some theoretical and practical implications at the organizational level are offered, describing how CG influences FP within the organization, and research limitations and future directions are presented.